Assessing the Organizational Communication Style and its Effect on Employees' Performance in the Case of Wachemo University - Endalkachew Desta; Zemede Chamiso (MultiTech Publisher, 2021)
In the case of Wachemo University, this paper looks into evaluating organizational communication style and how it affects employee performance. 261 sample respondents were given a standardized questionnaire as part of the study's survey methodology. The study's aims were achieved by combining the dependent variable, employee performance in the organization, with the independent variables completeness, correctness, consideration, clarity, conciseness, courtesy, and concreteness. Vice Presidents of Academic Affairs, Research and Community Service, and Administrative and Development are all involved in this investigation. The sample was chosen purposefully within each office: from the academic vice-president office, the colleges of business and economics, social science, and agricultural science were chosen; from the research and community service vice-president office, the following institutions were chosen: Community service directorate office, Research publication office, and Research directorate office. The finance office and Student service office were chosen from the administrative and development vice-president office. Following collection, the data was analyzed using tables and graphs that use descriptive statistics. Additionally, a multiple linear regression model was employed to investigate how changes in each of the study's independent factors affected how well the employees performed. The results demonstrate that every independent variable has a favorable and significant impact on how well an organization's employees perform. Affective commitment and the communication surrounding work and organization were both favorably impacted by social and emotional subjects that were discussed between superiors and subordinates. The organization should build a fluid communication style between different departments in order for them to better coordinate and cooperate in order to achieve the overall organizational goals, according to the results and recommendations